GM-033 Delphi study: adherence to treatment and quality of life in cancer associated thrombosis. (25th February 2017) - Rubio, AR; Perez, P; Jimenez, P; Monreal, M; Muñoz, A; Fernandez, C Suarez; Font, C; Lecumberri, R; Foncuberta, J; Otero, R
Abstract : Background: Venous thromboembolism (VTE) is a common complication in cancer patients. Non-adherence to anticoagulation therapy can lead to unsatisfactory health outcomes, and increase overall healthcare costs. Purpose: To assess the Delphi technique as a method for achieving convergence of opinion concerning adherence to anticoagulation therapy and quality of life in cancer patients with VTE. Material and methods: The Delphi technique was used to collect data from a panel of selected healthcare professionals, a multidisciplinary team of 27 experts (oncologists, haematologists, internal medicine experts, pulmonologists, emergency room physicians and hospital pharmacists). All were invited to answer an electronic questionnaire of 31 questions using a Likert scale (1, strongly disagree—4, strongly agree) in two rounds. A consensus was considered to have been reached when at least 70% of the panellists answered strongly agree/disagree on a recommendation. Any recommendation that did not obtain ≥70% agreement/disagreement was regarded. Results: According to the experts' opinions based on clinical daily practice, a positive Delphi consensus was reached on the following statements: a VTE diagnosis has an impact on quality of life (75%), adherence to anticoagulant treatment of VTE in cancer patients is critical (96%) and lack of adherence increases the recurrence of VTE (89%). A majority agreement was achieved for two statements: no instruments to measure quality of life in cancer patients with VTE are used (67%) and adherence to anticoagulant treatment of cancer patients with VTE is evaluated in clinical practice (56%). The experts agreed that low molecular weight heparin (LMWH) offered better compliance (33%). Conclusion: Expert consensus was reached about a VTE diagnosis having a negative impact on quality of life, adherence to treatment is important (because lack of adherence increases recurrence of VTE in cancer patients) and treatment with LMWH could increase adherence to treatment in patients with cancer associated thrombosis. No conflict of interest